Supernatural youth : the rise of the teen hero in literature and popular culture - Battis, Jes, 1979- (Lexington Books, 2011)
"Supernatural Youth: The Rise of the Teen Hero in Literature and Popular Culture, edited by Jes Battis, addresses the role of adolescence in fantastic media, adventure stories, cinema, and television aimed at youth. The goal of this volume is to analyze the ways in which young heroic protagonists are presented in such popular literary and visual texts. Supernatural Youth surveys a variety of sources whose young protagonists are placed in heroic positions, whether by magic, technology, prophecy, or other forces beyond their control. Series examined include Harry Potter, Buffy the Vampire Slayer, Veronica Mars, and Sabrina the Teenage Witch. Supernatural Youth, edited by Jes Battis, is essential for educators who work in the fields of English, media studies, women's studies, LGBT studies, and sociology, as well as undergraduate students who are interested in popular culture"--Provided by publisher